Psychological hesitation and its relationship to the accuracy of serving reception skills among Baghdad University volleyball team players - Obeid, Asst.L. Mustafa Ahmed; Khalifa, Asst.L. Abbas Hussein; Abdulkarim, Asst.L. Omar Walid (Sulaimani Journal for Humanities, 2025)
This study aims to determine the relationship between psychological frequency and the accuracy of receiving a serve in volleyball. The researchers used a descriptive approach, which is best suited to the research problem. The study sample consisted of 12 players from the University of Baghdad volleyball team. Ten players were selected purposively, and two were excluded from the research sample for use in a pilot study, as well as players who participate in volleyball at sports clubs. The sample size represented 83% of the original population. The researchers used the Psychological Frequency Scale developed by Firas Abdul Hussein (1999) for sports-related applications, which consists of 51 positive and negative items. The SPSS version 26 software was used to statistically extract the data. The results showed that the correlation coefficient for the three regions was (-0.72, -0.58, -0.65), which is higher than the critical value (0.497). This indicates a significant correlation between psychological frequency and the accuracy of serving and receiving skills in volleyball. This relationship is inverse, meaning that as the level of psychological frequency increases among the research sample, the accuracy of serving and receiving decreases, and vice versa. The study concluded that there is a significant inverse correlation between psychological frequency and the accuracy of serving and receiving in volleyball, confirming that psychological frequency negatively affects performance quality and weakens the player's ability to make decisions during skill execution. Therefore, the researchers recommended designing effective psychological training programs to reduce frequency and enhance confidence through relaxation techniques, mental visualization, decision-making under pressure, and improving focus using meditation and breath control, along with exercises that simulate the pressures of matches to improve psychological response.
Keywords: Volleyball; psychological frequency; receiving the serve